Gerenciamento de projetos: um enfoque em projetos utilizando o sistema CRM Lyd - Santos, Renan Silva dos (Universidade do Vale do Rio dos Sinos, 2019)
Managing projects is not an easy task to be accomplished, because it involves communication and information management between teams and stakeholders. This article aims to help the project manager and other users of the CRM System of a software development company to quickly obtain information about the projects and try to identify by means of the performance indicators theirs developed projects. This work, through a qualitative method, obtained results that showed that grouping project data in only one page and displaying the indicators helped the users' routine and demonstrating that their actions directly or indirectly impact the company's project performance.
Keywords: Gerenciamento de projetos; Sistema CRM Lyd; Project management; System CRM Lyd